Growth and production of Heliconia under different light conditions - Da Silva, Mayara Wesley; Ono, Elizabeth Orika [UNESP]; Santos, Maria Herbẽnia Lima Cruz; Cavalcante, Mãrkilla Zunete Beckmann; De Oliveira, Gertrudes Macãrio; Ferreira, Dulce Naiara Carvalho; Lopes, Caio Cesar (My University, 2017)
The use of shading screens of different colors can change the spectral quality of radiation and, as a consequence, the growth and production of crop plants. The aim of this study was to evaluate aspects of the growth, yield, and quality of floral stems of Heliconia psittacorum × H. spathocircinata 'Golden Torch' grown under different light conditions. The treatments consisted of four conditions: blue photoconversion screens (35%-40%); red photoconversion screens (18%-21%); black shading screens (45%-49%), and full sunlight. The experiment consisted of two parts. In the first, growth was assessed, whereas in the second, aspects related to the production and quality of floral stems were examined. The experimental design was in randomized blocks with split plots in time. Each plot contained six blocks, with 11 replications per block, giving a total of 66 pots per plot. The evaluations were performed at 30-day intervals over a 6-month period. In the analysis of growth, red screens contributed to the growth of the plants, increasing the number of shoots and leaves, and also plant height. The productivity and quality of floral stems was, however, highest in plants grown under blue and black screens. It can be concluded that, under the prevailing experimental conditions, the use of blue screens (35%-40%) and black screens (45%-49%) is suitable for production of the floral stems of 'Golden Torch' heliconia.
Keywords: Golden Torch; Heliconia psittacorum × H; Ornamental plant; Photoconversion screen; Spathocircinata